COMPARATIVE ANALYSIS OF MODERN FLOTATION REAGENTS IN BENEFICIATION OF COPPER-MOLYBDENUM ORES - N.I.Nosirov,; Z.T.Abdatova, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: The search for effective reagents for the flotation of non-ferrous metals from mineral raw materials is an actual problem. The article discusses the results of research on improving the technology of processing copper–molybdenum ores using a combined collector emulsion. The object of research was copper–molybdenum ore containing 0.43% copper and 0.0089% molybdenum. Copper minerals are represented by chalcopyrite 1.2% and chalcocite 0.015%, while covellite is present in a much smaller amount. The main mineral of molybdenum is molybdenite.The cycle of collective copper–molybdenum flotation includes the main flotation, control flotation, and three re-cleanings of concentrate. In the basic mode, the collective Cu–Mo concentrate was produced with the copper content of 16.25% with an extraction of 77.79% and with the molybdenum content of 0.45% with an extraction of 79.38%.Reaflot, thionocarbamate, and butyl xanthate were used in a ratio of 1:3:15 to prepare a combined collector agent. In order to produce the combined collector emulsion, the best degree of dispersion, which amounted to 99.5% of particles with a size of −3.6 μm, was chosen.During the Cu–Mo ore flotation using an optimally dispersed microemulsion of the combined collector agent, a collective Cu–Mo concentrate was obtained with a copper content of 18.2% with an extraction of 83.58%, and with a molybdenum content of 0.49% with an extraction of 88.46%.The use of a combined collector agent increases the extraction of copper into the collective Cu–Mo concentrate by 5.79%, while the extraction of molybdenum increases by 9.08%.